Preparation process of carbon adsorption ink
Through precise proportioning and addition of auxiliary materials, combined with advanced process technology, carbon adsorption ink blocks or ink strips with high iodine adsorption value are prepared, which solves the problem that traditional ink products fail to fully utilize the adsorption potential of activated carbon, and achieves significant adsorption performance and health care functions.
Patent Information
- Application Number
- CN202411808860.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional activated carbon or ink products have failed to fully tap and utilize the high adsorption potential of activated carbon, which limits its performance and effect in actual applications.
By accurately proportioning bamboo charcoal, pine smoke and peel glue, and adding a variety of auxiliary materials, combined with high-frequency vibration stirring, ancient ink making technology, multi-stage grinding technology, ultrasonic dispersion technology, intelligent temperature control and pressure sensing technology, a large number of carbon adsorption ink blocks or ink strips with high iodine adsorption value and stability are prepared.
It significantly improves the adsorption performance, writing fluency and health care functions of ink, can effectively absorb and decompose harmful substances in the room, improve indoor air quality, and provide users with a healthier and more environmentally friendly writing experience.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon adsorption ink, and in particular relates to a carbon adsorption ink preparation process. Background Art
[0002] In the conventional market, the iodine value (i.e., a quantitative indicator of adsorption capacity) of common activated carbon or related products is generally maintained at a level of about 100 mg / g. Iodine value, as a key parameter to measure the adsorption performance of activated carbon, directly reflects the material's adsorption capacity for specific substances (such as iodine). A high iodine value means that the activated carbon has a richer microporous structure and stronger adsorption capacity, which is crucial for applications such as removing harmful gases from the air and purifying water. However, traditional activated carbon or ink products are often limited to their basic adsorption functions and fail to fully explore and utilize the high adsorption potential of activated carbon, thereby limiting its performance and effects in practical applications. Summary of the invention
[0003] The purpose of the present invention is to provide a carbon adsorption ink preparation process in view of the existing problems.
[0004] The present invention is achieved through the following technical solutions: A process for preparing carbon adsorption ink, characterized in that it specifically comprises the following steps: a) preparing raw materials, including bamboo charcoal, pine soot and hide glue, wherein the raw materials are mixed in a specific ratio, namely, bamboo charcoal:pine soot:hide glue=4:3:4; this ratio can ensure the stability and adsorption performance of the ink, while giving the ink good writing fluency and color.
[0005] b) Adding auxiliary materials, including borneol, gold foil, musk, bear bile and at least ten kinds of carefully selected and proportioned Chinese herbal medicines, including but not limited to herbs with antibacterial, anti-inflammatory, antioxidant and other effects, and the proportion of each Chinese herbal medicine is accurately calculated to achieve the best synergistic effect and health care function; these auxiliary materials not only improve the quality and aroma of the ink, but also give the ink additional health care functions.
[0006] c) Preliminarily mixing all the raw materials in step a) and step b), and using high-frequency vibration stirring technology during the mixing process; the high-frequency vibration stirring technology can ensure uniform mixing of the raw materials and improve the stability and uniformity of the ink.
[0007] d) The raw materials after preliminary mixing are further ground, stirred, precipitated and filtered using the ancient ink-making process. The grinding process uses multi-stage grinding technology and combines it with ultrasonic dispersion technology to obtain pure and uniform ink raw materials. This step can ensure the fineness and purity of the ink and improve the writing performance and adsorption performance of the ink.
[0008] e) Before pressing and molding, the ink raw materials obtained in step d) are further blended, and intelligent temperature control technology is used to accurately control the temperature during the blending process; the intelligent temperature control technology can ensure the stability of the ink raw materials during the blending process and avoid the influence of temperature fluctuations on the ink performance.
[0009] f) Pressing and molding the ink raw materials blended in step e) to obtain a carbon adsorption ink block or a carbon adsorption ink stick having a specific shape and size, and using pressure sensing technology during the pressing process to monitor and control the pressure distribution in real time; the pressure sensing technology can ensure the uniformity and stability of the ink block or ink stick, and improve the quality and service life of the product.
[0010] g) Quality inspection and screening of the pressed carbon adsorption ink block or carbon adsorption ink strip, using high-precision spectral analysis technology to detect the composition and uniformity of the ink block to ensure that it meets specific quality standards and requirements. This step can ensure product quality and consistency, and improve user satisfaction and trust.
[0011] Furthermore, the iodine adsorption value of the bamboo charcoal in step a) is ≥800, and the viscosity of the hide glue in step a) is ≥12°E. Bamboo charcoal with a high iodine adsorption value can enhance the adsorption performance of the ink, while the high viscosity hide glue can ensure the stability and adhesion of the ink.
[0012] Furthermore, the sieve size used in the filtration process in step d) is 100 mesh, which can ensure the purity and fineness of the ink, remove impurities and particles, and improve the writing performance and adsorption performance of the ink.
[0013] Furthermore, the bamboo charcoal and pine smoke in step a) are treated with nanotechnology, which specifically includes the following steps, and the beneficial effects of each step are as follows: 1) Nano-scale crushing step: The bamboo charcoal and pine smoke raw materials are respectively fed into the air flow pulverizer, and the air flow speed is adjusted to 240-300 liters / minute. The raw materials are subjected to nano-scale crushing treatment to obtain nano bamboo charcoal and nano pine smoke powder with a particle size of 10-100 nanometers. The crushed nano particles are screened to remove particles with a particle size greater than 100 nanometers or less than 10 nanometers. Nano-scale crushing can increase the specific surface area of bamboo charcoal and pine smoke, and improve the adsorption performance and writing fluency of ink.
[0014] 2) Surface modification step: select chemical modifiers such as silane coupling agent, titanate coupling agent or high molecular polymer, and add them in an amount of 5%-9% of the mass of the nanoparticles. Disperse the nano bamboo charcoal and nano pine smoke powder in solvents such as ethanol, acetone or water to form a uniform suspension with a solid content of 20%-30%. Slowly add the chemical modifier under the condition of stirring speed of 650-800 rpm, and continue stirring for 1.2-1.8 hours to allow the modifier to be fully adsorbed on the surface of the nanoparticles. The chemical reaction is promoted by heating to 85-100 degrees Celsius, ultrasonic treatment for 1.5-2 hours or microwave radiation for 20-30 minutes to form a stable chemical bond. The suspension after filtering is washed 2-3 times with deionized water or ethanol and other solvents to remove unreacted modifiers and impurities. The vacuum drying method is used to dry the mixture at a temperature of 90-120 degrees Celsius and a pressure of 0.06-0.1 MPa for 12-16 hours to obtain chemically modified nano bamboo charcoal and nano pine smoke powder. Surface modification can improve the dispersibility and stability of nanoparticles, and improve the uniformity and writing performance of ink.
[0015] 3) Purification and drying step: purify the surface-modified nano bamboo charcoal and nano pine soot powder to remove unreacted modifiers, impurities and by-products. The purification efficiency is not less than 90%. Spray drying is used to dry the purified nanoparticles at an inlet temperature of 270-300 degrees Celsius and an outlet temperature of 100-120 degrees Celsius. The drying time is controlled to avoid agglomeration and structural damage of the nanoparticles. The drying time is usually 13-15 hours. Purification and drying can ensure the purity and stability of the nanoparticles and improve the quality and performance of the ink.
[0016] Furthermore, the carbon adsorption iodine value of the carbon adsorption ink block or carbon adsorption ink stick is greater than 300 mg / g, and it not only has the use value and collection value of Hui ink, such as black and bright color, fine texture, smooth writing, etc., but also has a significant carbon adsorption function, which can effectively absorb harmful substances such as formaldehyde, sulfide, ammonia, odor, etc., and provide users with a healthier and more environmentally friendly writing experience. This carbon adsorption ink block or carbon adsorption ink stick not only has the excellent characteristics of traditional Hui ink, but also has a unique carbon adsorption function, which can improve indoor air quality and protect the health of users.
[0017] Compared with the prior art, the present invention has the following advantages: 1. By accurately mixing bamboo charcoal, pine soot and hide glue, and adding a variety of carefully selected auxiliary materials, the present invention not only improves the stability and adsorption performance of the ink, but also gives the ink good writing fluency, color and unique health care functions.
[0018] 2. Nano-scale pulverization of bamboo charcoal and pine smoke significantly increases their specific surface area, thereby improving the adsorption performance and writing fluency of the ink. This nano-scale treatment enables the ink to more effectively absorb and fix harmful substances such as formaldehyde, sulfide, ammonia and odor.
[0019] 3. The high-frequency vibration stirring technology is used to ensure the uniform mixing of raw materials and improve the stability and uniformity of the ink. The combination of the ancient ink-making process with modern multi-level grinding technology and ultrasonic dispersion technology makes the ink raw materials purer and more uniform, further improving the fineness and writing performance of the ink. In the pressing process, the intelligent temperature control technology and pressure sensing technology are used to ensure the uniformity and stability of the ink block or ink strip, and improve the quality and service life of the product.
[0020] 4. The carbon adsorption ink block or ink strip after pressing is subjected to high-precision spectral analysis to detect its composition and uniformity, ensuring that the product meets specific quality standards and requirements. The strict screening process ensures that each ink block or ink strip has excellent carbon adsorption capacity and stable writing performance.
[0021] 5. The carbon adsorption ink block or ink stick of the present invention not only inherits the excellent characteristics of traditional Huizhou ink, such as black and bright color, fine texture, and smooth writing, but also has a significant carbon adsorption function. This carbon adsorption function enables the ink block or ink stick to continuously absorb and decompose harmful substances in the room during use, improve indoor air quality, and provide users with a healthier and more environmentally friendly writing environment. DETAILED DESCRIPTION Example 1
[0022] A process for preparing carbon adsorption ink, characterized in that it specifically comprises the following steps: a) preparing raw materials, including bamboo charcoal, pine soot and hide glue, wherein the raw materials are mixed in a specific ratio, namely, bamboo charcoal:pine soot:hide glue=4:3:4; this ratio can ensure the stability and adsorption performance of the ink, while giving the ink good writing fluency and color.
[0023] b) Adding auxiliary materials, including borneol, gold foil, musk, bear bile and at least ten kinds of carefully selected and proportioned Chinese herbal medicines, including but not limited to herbs with antibacterial, anti-inflammatory, antioxidant and other effects, and the proportion of each Chinese herbal medicine is accurately calculated to achieve the best synergistic effect and health care function; these auxiliary materials not only improve the quality and aroma of the ink, but also give the ink additional health care functions.
[0024] c) Preliminarily mixing all the raw materials in step a) and step b), and using high-frequency vibration stirring technology during the mixing process; the high-frequency vibration stirring technology can ensure uniform mixing of the raw materials and improve the stability and uniformity of the ink.
[0025] d) The raw materials after preliminary mixing are further ground, stirred, precipitated and filtered using the ancient ink-making process. The grinding process uses multi-stage grinding technology and combines it with ultrasonic dispersion technology to obtain pure and uniform ink raw materials. This step can ensure the fineness and purity of the ink and improve the writing performance and adsorption performance of the ink.
[0026] e) Before pressing and molding, the ink raw materials obtained in step d) are further blended, and intelligent temperature control technology is used to accurately control the temperature during the blending process; the intelligent temperature control technology can ensure the stability of the ink raw materials during the blending process and avoid the influence of temperature fluctuations on the ink performance.
[0027] f) Pressing and molding the ink raw materials blended in step e) to obtain a carbon adsorption ink block or a carbon adsorption ink stick having a specific shape and size, and using pressure sensing technology during the pressing process to monitor and control the pressure distribution in real time; the pressure sensing technology can ensure the uniformity and stability of the ink block or ink stick, and improve the quality and service life of the product.
[0028] g) Quality inspection and screening of the pressed carbon adsorption ink block or carbon adsorption ink strip, using high-precision spectral analysis technology to detect the composition and uniformity of the ink block to ensure that it meets specific quality standards and requirements. This step can ensure product quality and consistency, and improve user satisfaction and trust.
[0029] The iodine adsorption value of the bamboo charcoal in step a) is 873, and the viscosity of the hide glue in step a) is 13.6°E. The bamboo charcoal with a high iodine adsorption value can enhance the adsorption performance of the ink, while the hide glue with a high viscosity can ensure the stability and adhesion of the ink.
[0030] The sieve size used in the filtration process in step d) is 100 mesh, which can ensure the purity and fineness of the ink, remove impurities and particles, and improve the writing performance and adsorption performance of the ink.
[0031] The bamboo charcoal and pine smoke in step a) are treated by nanotechnology, specifically comprising the following steps, each of which has the following beneficial effects: 1) Nano-scale pulverization step: The bamboo charcoal and pine smoke raw materials are respectively fed into the air flow pulverizer, and the air flow speed is adjusted to 260 liters / minute. The raw materials are subjected to nano-scale pulverization to obtain nano bamboo charcoal and nano pine smoke powder with a particle size of 30-60 nanometers. The crushed nanoparticles are screened to remove particles with a particle size greater than 60 nanometers or less than 30 nanometers. Nano-scale pulverization can increase the specific surface area of bamboo charcoal and pine smoke, and improve the adsorption performance and writing fluency of ink.
[0032] 2) Surface modification step: Select chemical modifiers such as silane coupling agent, titanate coupling agent or high molecular polymer, and add 8% of the mass of nanoparticles. Disperse nano bamboo charcoal and nano pine smoke powder in solvents such as ethanol, acetone or water to form a uniform suspension with a solid content of 24%. Slowly add chemical modifiers at a stirring speed of 700 rpm, and continue stirring for 1.5 hours to allow the modifiers to fully adsorb on the surface of nanoparticles. Promote chemical reactions by heating to 90 degrees Celsius, ultrasonic treatment for 2 hours or microwave radiation for 30 minutes to form stable chemical bonds. Filter the treated suspension, wash it 3 times with deionized water or ethanol and other solvents to remove unreacted modifiers and impurities, and use vacuum drying method to dry it at a temperature of 110 degrees Celsius and a pressure of 0.08 MPa for 12 hours to obtain chemically modified nano bamboo charcoal and nano pine smoke powder. Surface modification can improve the dispersibility and stability of nanoparticles, and improve the uniformity and writing performance of ink.
[0033] 3) Purification and drying step: The surface-modified nano bamboo charcoal and nano pine soot powders are purified to remove unreacted modifiers, impurities and by-products. The purification efficiency is 93%. The purified nanoparticles are dried by spray drying at an inlet temperature of 280 degrees Celsius and an outlet temperature of 100 degrees Celsius. The drying time is controlled to avoid agglomeration and structural damage of the nanoparticles. The drying time is 15 hours. Purification and drying can ensure the purity and stability of the nanoparticles and improve the quality and performance of the ink.
[0034] The carbon adsorption ink block or carbon adsorption ink stick has a carbon adsorption iodine value of 363 mg / g, and not only has the use value and collection value of Hui ink, such as black and bright color, fine texture, smooth writing, etc., but also has a significant carbon adsorption function, which can effectively absorb harmful substances such as formaldehyde, sulfide, ammonia, odor, etc., providing users with a healthier and more environmentally friendly writing experience. This carbon adsorption ink block or carbon adsorption ink stick not only has the excellent characteristics of traditional Hui ink, but also has a unique carbon adsorption function, which can improve indoor air quality and protect the health of users.
[0035] The performance indicators of the carbon adsorption ink preparation process embodiment 1 are as follows:
[0036] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. A process for preparing carbon adsorption ink, characterized in that: The specific steps include: a) preparing raw materials, including bamboo charcoal, pine soot and hide glue, wherein the raw materials are mixed in a specific ratio, i.e., bamboo charcoal: pine soot: hide glue = 4:3:4; b) Adding auxiliary materials, including borneol, gold foil, musk, bear bile and at least ten kinds of carefully selected and proportioned Chinese herbal medicines, including but not limited to herbs with antibacterial, anti-inflammatory, antioxidant and other effects, and the proportion of each Chinese herbal medicine is accurately calculated to achieve the best synergistic effect and health care function; c) preliminarily mixing all the raw materials in step a) and step b), and using high-frequency vibration stirring technology during the mixing process; d) The raw materials after preliminary mixing are further ground, stirred, precipitated and filtered using the ancient ink making process, wherein the grinding process uses multi-stage grinding technology and combines ultrasonic dispersion technology to obtain pure and uniform ink raw materials; e) before pressing and molding, further blending the ink raw material obtained in step d) and using intelligent temperature control technology to accurately control the temperature during the blending process; f) pressing the ink raw material prepared in step e) to obtain a carbon adsorption ink block or a carbon adsorption ink strip having a specific shape and size, and using pressure sensing technology to monitor and control pressure distribution in real time during the pressing process; g) Carry out quality inspection and screening on the pressed carbon adsorption ink block or carbon adsorption ink strip, and use high-precision spectral analysis technology to detect the composition and uniformity of the ink block to ensure that it meets specific quality standards and requirements.
2. The process for preparing carbon adsorption ink according to claim 1, characterized in that: The iodine adsorption value of the bamboo charcoal in step a) is ≥800, and the viscosity of the hide glue in step a) is ≥12°E.
3. The process for preparing carbon adsorption ink according to claim 1, characterized in that: The sieve size used in the filtration process in step d) is 100 mesh.
4. The process for preparing carbon adsorption ink according to claim 1, characterized in that: The bamboo charcoal and pine smoke in step a) are treated with nanotechnology, specifically comprising the following steps: 1) Nano-scale pulverization step: the bamboo charcoal and pine smoke raw materials are respectively fed into an air flow pulverizer, and the air flow speed is adjusted to 240-300 liters / minute, and the raw materials are subjected to nano-scale pulverization treatment to obtain nano bamboo charcoal and nano pine smoke powders with a particle size of 10-100 nanometers, and the pulverized nano particles are screened to remove particles with a particle size greater than 100 nanometers or less than 10 nanometers; 2) Surface modification step: select chemical modifiers such as silane coupling agent, titanate coupling agent or high molecular polymer, and add them in an amount of 5%-9% of the mass of the nanoparticles. Disperse the nano bamboo charcoal and nano pine smoke powder in solvents such as ethanol, acetone or water to form a uniform suspension with a solid content of 20%-30%. Slowly add the chemical modifier under the condition of stirring speed of 650-800 rpm, and continue stirring for 1.2-1.8 hours to allow the modifier to be fully adsorbed on the surface of the nanoparticles. Heating to 85-100 degrees Celsius, ultrasonic treatment for 1.5-2 hours or microwave radiation for 20-30 minutes to promote chemical reaction, form stable chemical bonds, filter the treated suspension, wash 2-3 times with deionized water or ethanol and other solvents to remove unreacted modifiers and impurities, and dry for 12-16 hours at a temperature of 90-120 degrees Celsius and a pressure of 0.06-0.1 MPa by vacuum drying to obtain chemically modified nano bamboo charcoal and nano pine smoke powder; 3) Purification and drying step: The surface-modified nano bamboo charcoal and nano pine smoke powder are purified to remove unreacted modifiers, impurities and by-products. The purification efficiency is not less than 90%. The purified nanoparticles are dried by spray drying at an inlet temperature of 270-300 degrees Celsius and an outlet temperature of 100-120 degrees Celsius. The drying time is controlled to avoid agglomeration and structural damage of the nanoparticles. The drying time is usually 13-15 hours.
5. The carbon adsorption ink block or carbon adsorption ink strip prepared by the process for preparing carbon adsorption ink according to any one of claims 1 to 4, characterized in that: The carbon adsorption iodine value of the carbon adsorption ink block or carbon adsorption ink stick is greater than 300 mg / g. It not only has the use value and collection value of Hui ink, such as black and bright color, fine texture, smooth writing, etc., but also has significant carbon adsorption function, which can effectively absorb harmful substances such as formaldehyde, sulfide, ammonia, odor, etc., providing users with a healthier and more environmentally friendly writing experience.